PENINGKATAN HASIL BELAJAR IPS KELAS VI DENGAN MODEL PEMBELAJARAN KOOPERATIF TIPE EXAMPLES NON EXAMPLES DI SDN 007 TERATAK AIR HITAM KECAMATAN SENTAJO RAYA - Yanson Yanson (JURNAL PAJAR (Pendidikan dan Pengajaran), 2018)
Social science subjects are arranged in a systematic, comrehensive, and integrated in the learning processtowards succes in the life in the community. With the approach it is expected that learners will acquire a broaderunderstanding and dept in the field of science related. This reseach method in classroom action reseach usingtwo cycle the end of each cycle is given daily test given to students in as musc as 19 persons in the class VI SDN007 Teratak Air Hitam sub-district Sentajo Raya. The reseach result obtained the result of the study preliminarydata 65,3 increase by an average of learning outcomes of IPS to 75 in cycle I. I the second cycle obtained anaverage of 90 with the learning cycle I is 14,58% and from cycle I to cycle II amounted of 37,89%. Activities theteacher looks at the cycle I the first meeting of 66,67% with enough categories, while at the second meetingincreased so that the average obtained by 75%, with good categories. In cycle II it turns out that teacherlearning has increased sothat the obtained average 83,3% with good categories, while at the second meetingcycle II obtained average to 91,67 % with very good categories. Data activity studens looks at the cycle I the firsmeeting obatined an average of 61,11 with lee categories, at the second meeting obtained an average 72,22%with enough categories. In the second cycle obtained an average of the first meeting of 80,56% with goodcategory, while in the second meeting with average to 91,67% with the cagory very well. So it can be concludedthat the applicatin of cooperative medel type example non examplescan improve learning outcomes IPS.